Crystallization study of molybdate phosphate glasses by thermal analysis - Ottoboni, Fabiola S.; Poirier, Gael; Cassanjes, Fabia C.; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2009)
Vitreous samples were prepared in the binary system NaPO(3)-MoO(3) and their characteristic temperatures were determined by Differential Scanning Calorimetry. Glasses with high amounts of MoO(3) (>45 mol%) exhibit an intense crystallization peak and the composition 50 NaPO(3)-50 MoO(3) was chosen for the crystallization study. Two different methods based on thermal analyzes were used to determine the mechanism of crystallization in these molybdenum-phosphate glasses. In the first procedure, thermal analyses by DTA were performed on samples with different grain sizes and the crystallization tendency deduced in function of superficial area. The second method used the classical non-isothermal crystallization study: DSC measurements were performed under several heating rates to access activation energy for crystallization and Avrami parameter n. Critical cooling rate was calculated and compared with experimental data obtained from DTA analysis upon cooling. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystallization; Glass ceramics; Phosphates